Pre-operative diagnosis of thyroid cancer : clinical, radiological and pathological correlation - Cairncross, Lydia Leone (Department of Surgery, 2014)
Primary Aim: assess the accuracy of pre operative diagnosis of thyroid cancer in a single centre. Secondary Aims: evaluate the impact of preoperative diagnosis on surgical interventions for thyroid carcinoma; develop locally applicable guidelines for patients with nodular disease of the thyroid.